ANTINOCICEPTIVE, ANTI-INFLAMMATORY EFFECTS AND SAFETY OF ZIZIPHUS MISTOL FRUITS (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Ziziphus mistol Griseb. (Rhamnaceae), popularly known as “mistol,” is widely distributed throughout Perú, Bolivia, Paraguay and Argentina. Its fruit is consumed in different forms in several argentinean communities and used against biliary colic, dysentery, cold stomach and diseases of the respiratory system characterized by pain and inflammation. The present study was carried out to investigate the medicinal properties and safety of Ziziphus mistol (mistol) fruits ethanol and aqueous extracts and arrope. Antinociceptive activity was assessed using the formalin, acetic acid-induced writhing and tail-ﬂick tests in rats. Anti-inﬂammatory effects were determined through carrageenan induced edema test and cotton pellet-induced granuloma formation, in rats. The safety was evaluated with test of acute toxicity (48 hours) and sub-chronic toxicity (91 days). All extracts (1,000 mg/kg b.w.) showed significant inhibition (P <0.05) in the three model of pain experimentally induced in comparison to control. In a combination test using naloxone, diminished analgesic activity of aqueous extract and arrope were observed, indicating that their antinociceptive activity is connected with the opioid receptors. At dose 1000 mg/kg bw, the aqueous extract and arrope showed higher anti-inflammatory activity than the ethanol extract, in carrageenan and cotton pellet granuloma model used. In the acute toxicity study, a single dose of 4000 and 8000 mg/kg b.w., produced no mortality and no clinical signs of disease were observed after 48 hours. In the sub-chronic toxicity study the extracts no caused significant visible signs of toxicity, nor mortality for 91 consecutive days of treatment. Extracts and arrope of Z. mistol fruits could be good source of antinociceptive and anti-inflammatory agents because of its good activity and safety.